Survei Motivasi Belajar Pendidikan Jasmani pada Siswa Sekolah Luar Biasa di Kabupaten Karawang - Iip Ripai Azhuri; Tedi Purbangkara; Nana Suryana Nasution (Universitas Singaperbangsa, 2021)
MOTIVATION SURVEY TO LEARN PHYSICAL EDUCATION IN SLB STUDENTS OF KARAWANG DISTRICT. This study aims to determine the level of motivation to learn Physical Education in SLB students in Karawang Regency. The approach used in this research is quantitative, with survey methods and research design using cross sectional. The population in this study were all students of class VIII at the State Special School (SLB) and Special School (SLB) B Tunas Harapan, Karawang Regency, totaling 20 students, while the samples were taken according to the total population with a total sampling technique, obtained by class VIII from The two SLBs total 20 students as a class who will be given a questionnaire about student learning motivation. The data were processed using Microsoft Excel software. The results of this study indicate that the level of student motivation in physical education learning shows a percentage of learning motivation as much as 40% with moderate criteria. So it can be concluded that the level of student motivation in Physical Education learning can increase if the teacher is able to present the material well and fun, providing teaching through the form of games so that students do not feel bored when the learning takes place. Key words : Learning Motivation, SLB, Phsycal Education.